Information Security with Smart Hydrogels: Photo-Patterning and Multi-Stimuli Responsive Structural Color - Guo, Xiaoyu; Li, Ying; Hanif, Farzana; Zhu, Linhai; Kong, Miao; Zhang, Shufen; Zhang, Yuang; Tang, Bingtao (Nano-Micro Letters, 2026)
Photonically structured colors, characterized by high resolution and dynamic responsiveness, hold promising prospects in the field of information security. However, conventional patterning methods are often limited by high equipment costs and monotonous color outputs, which restrict their widespread adoption. To address these issues, this paper proposes a novel multi-color patterning method based on light-induced chemical crosslinking. By introducing light-initiated crosslinking molecules into anti-opal hydrogels, we developed a film that can be further regulated by photo-curing, enabling a “film formation first, then patterning” approach. The structural color hydrogels created using this method can display multi-color patterns, with a minimum line width of 15 μm, significantly enhancing their information-carrying capacity. Moreover, ultraviolet radiation can increase the degree of cross-linking, thereby inhibiting swelling behavior, enhancing tensile strength, reducing elongation at break, and causing the color of the inverse opal structure to shift toward blue or disappear. With inherent responsiveness to stress, temperature, and solvents, this approach enables dynamic information display and has excellent stability (able to cycle stably for more than 100 times). This work introduces a new method for patterning stimulus-responsive structural colors and opens up new possibilities for their use in applications such as ink-free printing, information encryption, and anti-counterfeiting. Highlights: 1 A light-induced crosslinking strategy enables multi-color patterning of anti-opal hydrogel with a minimum line width of 15 μm, significantly enhancing information capacity. 2 Control film crosslinking degree via UV irradiation allows adjust swelling, mechanical and optical properties of various stimulus-responsive structural color films simultaneously. 3 A "film formation first, then patterning" approach provides a new train of thought for dynamic information encryption, security and ink-free printing.